0663 Association of Insomnia Phenotypes based on Objective Sleep Duration with Suicide Attempts, Ideation and Completion. (25th May 2022) - Saulnier, Kevin; Singh, Rupsha; Lenker, Kristina; Calhoun, Susan; Liao, Duanping; Bixler, Edward; Vgontzas, Alexandros; Fernandez-Mendoza, Julio
Abstract: Introduction: Sleep disturbances, including insomnia and short sleep duration, are known risk factors for suicidal ideation, attempts, and death. Insomnia is a heterogeneous disorder, with phenotypes of short and normal sleep duration based on objective sleep measures showing differential pathophysiology, natural course, cardiometabolic and neurocognitive morbidity. However, little is known about the association of these insomnia phenotypes with suicidality in adults. Methods: We analyzed data from the Penn State Adult Cohort (N = 1741, M age = 52.46, SD = 13.43, 57.4% female), a randomly selected population-based sample who underwent a thorough clinical history and in-lab polysomnography (PSG). Suicidality was ascertained by a lifetime history of suicide attempts, suicidal ideation or suicide as cause of death by December 31 2018 (n = 102). Insomnia symptoms were defined as a complaint of moderate-to-severe difficulties initiating or maintaining sleep, early morning awakening and non-restorative sleep, or chronic insomnia (n = 719). Short sleep duration was defined as < 6-h of in-lab PSG-measured sleep (n = 879). Binary logistic regression was used to examine the association between insomnia phenotypes with suicidality, while controlling for sex, age, race/ethnicity, and medical and psychiatric comorbidities. Given the low suicidality prevalence in this sample, 1000 bootstrapped samples were drawn to provide stable estimates. Results: Compared to normal sleepers who slept > 6-h, subjects with insomnia symptoms who slept < 6-h and those who slept > 6-h were associated with 1.96-fold (95%CI = 1.04-4.00) and 2.46-fold (95%CI = 1.30-5.04) increased odds of suicidality, respectively. After further adjusting for substance use, subjects with insomnia symptoms who slept < 6-h and those who slept > 6-h were associated with 1.72-fold (95%CI = 0.90-3.58) and 2.22-fold (95%CI = 1.15-4.60) increased odds of suicidality, respectively. Normal sleepers who slept < 6-h were not associated with significantly increased odds of suicidality (OR = 1.32; 95%CI = 0.56-2.94). Conclusion: Adults with insomnia, particularly those with normal sleep duration, were associated with increased suicidality. These data further support that objectively-defined insomnia phenotypes may confer risk for differential adverse health outcomes (e.g., cardiometabolic vs. psychopathologic) via distinct mechanistic pathways. Support (If Any): American Heart Association (14SDG19830018)